1999
DOI: 10.1016/s0168-1702(99)00023-4
|View full text |Cite
|
Sign up to set email alerts
|

Growth behavior of bovine herpesvirus-1 in permissive and semi-permissive cells

Abstract: Bovine herpesvirus-1 (BHV-1) can replicate well in bovine-derived cell lines such as Madin Darby bovine kidney (MDBK) but grows poorly in hamster lung (HmLu-1). Virus replication, DNA synthesis, and immediate-early gene expression are severely restricted in HmLu-1. We compared adsorption and penetration of BHV-1 in permissive MDBK and semi-permissive HmLu-1 cells. At a low multiplicity of infection, BHV-1 attached to permissive MDBK cells twice as much as to HmLu-1. The presence of heparin inhibited the attach… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
21
0

Year Published

2000
2000
2017
2017

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 11 publications
(21 citation statements)
references
References 42 publications
0
21
0
Order By: Relevance
“…20 Myxoma virus, a rabbit poxvirus with a similar restricted tropism, functions as an oncolytic virus in human tumor cells bearing deficiencies in type I IFN and tumor necrosis factor-a (TNFa) pathways. 23,24 Before investigating the oncolytic capacity of BHV-1, we first confirmed the restriction of normal human cells against BHV-1 replication and CPE induction.…”
Section: Bhv-1 Replication Is Restricted In Normal Human Cellsmentioning
confidence: 99%
See 1 more Smart Citation
“…20 Myxoma virus, a rabbit poxvirus with a similar restricted tropism, functions as an oncolytic virus in human tumor cells bearing deficiencies in type I IFN and tumor necrosis factor-a (TNFa) pathways. 23,24 Before investigating the oncolytic capacity of BHV-1, we first confirmed the restriction of normal human cells against BHV-1 replication and CPE induction.…”
Section: Bhv-1 Replication Is Restricted In Normal Human Cellsmentioning
confidence: 99%
“…19 One of the interesting features of BHV-1 is its strict host range compared with other herpesviruses, including HSV-1. Of particular interest is the inability of BHV-1 to productively infect human cells, 20 supported by the lack of reports of either productive BHV-1 infection or even 21 In this study, we determined the ability of BHV-1 to replicate, cause cytopathic effects and affect cellular viability in a panel of normal, immortalized and transformed human cells from a variety of histological origins. We found that BHV-1 replicates and induces cytopathic effects in a wide subset of immortalized and transformed cells, thus decreasing cellular viability, but is significantly restricted in normal cells.…”
Section: Introductionmentioning
confidence: 97%
“…1E, G and I for MDBK, CER and CRIB cells, respectively. In fact, there are many advantages in using serum-free culture systems; first it has been suggested that cells cultured without serum/protein seems to be more favourable for viral infection than cultured by using the serum-supplemented medium; second bovine serum may contains viral inhibitors, such proteases, that decreases the virus stability; and third bovine serum may contains exogenous pathogens and also prions [7,13,14,15] .…”
Section: Resultsmentioning
confidence: 99%
“…Murata et al ( Murata T et al 1999 ) studied the effect of the MOI in the production of BoHV-1 in MDBK and found that the titer of the virus did not differ in view of the MOI used, but in HmLu cells, there is an important effect of the MOI. In 293 cells infected by adenovirus, the MOI had a progressive effect on viral production both in culture and in stationary MCs ( Kapil S, Basaraba RJ.…”
Section: Discussionmentioning
confidence: 99%